Assessing the Macroeconomic Impact of Water Supply Restrictions Through an Input–Output Analysis - Jaume Freire-González (Water Resources Management, 2011)
Water supply restrictions due to droughts generate significant costs to many economic agents. Although these costs are difficult to assess, this article presents a methodology to quantify, from a general equilibrium perspective, the macroeconomic impact of water supply restrictions through the estimation of aggregate production functions that include water consumption by sectors. Simulations with an Input-output model suggest a loss of 0.34% of GDP in the case of modest restrictions on the water supply and 2.8% in the case of more extreme restrictions for 2005 for the Catalonia region in Spain.
Keywords: 330